IRP2 as a potential modulator of cell proliferation, apoptosis and prognosis in nonsmall cell lung cancer. Issue 4 (13th April 2017) - Khiroya, Heena; Moore, Jasbir S.; Ahmad, Nabeel; Kay, Jamie; Woolnough, Kerry; Langman, Gerald; Ismail, Iyad; Naidu, Babu; Tselepis, Chris; Turner, Alice M.
IREB2 is a gene that produces iron regulatory protein 2 (IRP2), which is critical to intracellular iron homeostasis and which relates to the rate of cellular proliferation. IREB2 lies in a lung cancer susceptibility locus. The aims were to assess 1) the relationship between iron loading, cell proliferation and IRP2 expression in lung cancer; 2) the potential of iron related pathways as therapeutic targets; and 3) the relevance of IRP2 in operated lung cancer patients. Cells of two nonsmall cell cancer (NSCLC) lines and primary bronchial epithelial cells (PBECs) were cultured with and without iron; and proliferation, apoptosis and migration were assessed. Reverse transcriptase PCR and Western blot were used to assess expression of iron homeostasis genes/proteins. Iron chelation and knockdown of IREB2 were used in vitro to explore therapeutics. A cohort of operated NSCLC patients was studied for markers of systemic iron status, tumour IRP2 staining and survival. Iron loading caused cell proliferation in cancer cell lines, which were less able to regulate IREB2 expression than PBECs. Iron chelation resulted in a return of proliferation rates to baseline levels; knockdown of IREB2 had a similar effect. IRP2-positive tumours were larger (p=0.045) and higher percentage staining related to poorer survival (p=0.079). Loss of iron regulation represents a poor prognostic marker in lung cancer. Iron loading causes cell proliferation in lung cancer. Iron chelation can return proliferation rates to baseline http://ow.ly/zkes3093yYF